Phosphorylation of Sli15 by Ipl1 is important for proper CPC localization and chromosome stability in Saccharomyces cerevisiae. - Vasso Makrantoni; Stephen J Corbishley; Najma Rachidi; Nicholas A Morrice; David A Robinson; Michael J R Stark (PLoS ONE)
The chromosomal passenger complex (CPC) is a key regulator of eukaryotic cell division, consisting of the protein kinase Aurora B/Ipl1 in association with its activator (INCENP/Sli15) and two additional proteins (Survivin/Bir1 and Borealin/Nbl1). Here we have identified multiple sites of CPC autophosphorylation on yeast Sli15 that are located within its central microtubule-binding domain and examined the functional significance of their phosphorylation by Ipl1 through mutation of these sites, either to non-phosphorylatable alanine (sli15-20A) or to acidic residues to mimic constitutive phosphorylation (sli15-20D). Both mutant sli15 alleles confer chromosome instability, but this is mediated neither by changes in the capacity of Sli15 to activate Ipl1 kinase nor by decreased efficiency of chromosome biorientation, a key process in cell division that requires CPC function. Instead, we find that mimicking constitutive phosphorylation of Sli15 on the Ipl1 phosphorylation sites causes delocalization of the CPC in metaphase, whereas blocking phosphorylation of Sli15 on the Ipl1 sites drives excessive localization of Sli15 to the mitotic spindle in pre-anaphase cells. Consistent with these results, direct interaction of Sli15 with microtubules in vitro is greatly reduced either following phosphorylation by Ipl1 or when constitutive phosphorylation at the Ipl1-dependent phosphorylation sites is mimicked by aspartate or glutamate substitutions. Furthermore, we find that mimicking Ipl1 phosphorylation of Sli15 interferes with the 'tension checkpoint'--the CPC-dependent mechanism through which cells activate the spindle assembly checkpoint to delay anaphase in the absence of tension on kinetochore-microtubule attachments. Ipl1-dependent phosphorylation of Sli15 therefore inhibits its association with microtubules both in vivo and in vitro and may negatively regulate the tension checkpoint mechanism.